Originally Posted by

**Fratricide** I had another crack at it this morning, but still didn't get any further. I would try substituting w = (t-2)/2 and z = t into the first equation and solving for x and y, but when I substituted those x and y values into the other equations I would always end up with "x - x" or "y - y":

x + y + t + (t-2)/2 = 4

2x + 2y + 2t + t - 2 = 4

2x + 2y + 3t = 6

2x = 6 - 3t - 2y

x = 3 - (3t/2) - y

Substituting back into equation 1 I get:

3 - (3t/2) **- y + y** + z + w = 4

From there I could only solve for z or w, both of which I already have the values for. I also tried substituting that value for x into the second equation, but turned up nothing.

For our reference, the answers are:

z = t

y = (-3(t + 2))/4

x = (26 - 3t)/4

w = (t - 2)/2

And for the second part of the question:

x = -4, y = -12, z = 14